The Effect of Technology-based Interventions on the Performance of First Year University Statistics Students. Issue 2 (4th May 2018) - Reyneke, Fransonet; Fletcher, Lizelle; Harding, Ansie
Abstract : The study in this paper reports on whether an online homework system in combination with a flipped classroom has a positive effect on success rates of first year statistics students. Departing from a traditional teaching model (Baseline), the technology-based intervention strategies implemented were firstly the Aplia™ interactive online homework system (Phase 1) and then, in addition, the flipped classroom (Phase 2). In the flipped classroom model, the transfer of information took place by pre-reading and pre-class Aplia™ homework assignments. This approach intended to allow more quality time to be spent on revisiting difficult concepts and engaging in problems inside the lecture hall, thus enhancing the learning process. The average final marks of the three cohorts were compared using an ANOVA test. Chi-square tests were used to evaluate the effects of the changing teaching models from Baseline through Phase 1 to Phase 2. The success rates of three different cohorts (n = 1485, 1343 and 1466 respectively), consisting of only first-time statistics students with a Grade 12 mathematics mark of at least 60%, were assessed. For Phase 1 compared with the Baseline the increase in the success rate was insignificant, but the success rates for Phase 2 compared with both Phase 1 and Baseline improved significantly with a small to medium effect size, because of the very large samples. The practical importance of this is that the number of successful students increased by more than 100 from Phase 1 to Phase 2 and more than 130 from Baseline to Phase 2. A significant relationship was also found between the different cohorts and their mark distributions, confirming that the online homework system in combination with the flipped classroom in particular is effective in increasing the success rate.